Comparative Study of Clinker’s Transformation at Different Temperature Zone During Cement Production - Mohd Sobri, Idris; Khairul Nizar, Ismail; Shamsul Baharin, Jamaludin; Che Mohd Ruzaidi, Ghazali; Kamarudin, Hussin (Science Publications, 2008)
Link to publisher's homepage at http://scipub.org/scipub/index.php